DEVELOPMENT OF BANANA STEM, CHICKPEA PLANT BASED MEAT - Dr. M. Niharika,; Dr. D. Madhavi,; Dr. G. Sireesha,; Bhargavi Savalapurapu, (The Bioscan, 2025)
Plant-based meat (PBM) is gaining attention due to environmental, health, and welfare concerns. Food Structure methods like extrusion and shear cell are studied, along with improvements in appearance, flavor, safety controls, and protein sources. In order to develop protein based meat replacement with a rich fiber food; this current study we used banana stem, chick peas, Psyllium husk and binding as tapioca flour, spice ingredients for developing a BCPM (Banana stem, Chickpea Plant based Meat). The plant based meat was developed by extrusion and solar drying technology. The proximate composition and sensory analysis of the developed three samples (T1, T2 & T3) were studied; among these three variations T3 showed good sensory acceptance in sensory analysis. The functional properties of developed meat analogue variation 2 and 3 having good water holding capacity. On the other hand it contains 263 kcal of energy, 58.5 gm of carbohydrates, 17 gm of Protein, 5 gm of fat, 16 gm of fiber , 3.8 % moisture, and 99 mg of calcium; when compared to traditional animal meat the developed plant based meat analogue was good in energy, carbohydrate and calcium content. The morphological and textural studies of plant-based meat exhibit comparable characteristics to the available animal meats. Shelf life studies was carried out up to 4 months with different time intervals; the total bacterial counts of developed BCPM is at the end of the best before date varied greatly from below 1.8, it indicates no microbial spoilage was noticed during the storage period. The study emphasized that chick peas, banana stem and Psyllium husk combination would make a suitable plant based meat.